Toward an Integrative Framework of Dynamic Capabilities in Innovation-based Public Services: Empirical Analysis in Taiwan. Issue 1 (June 2019) - Fu, Kai-Jo; Chang, Teng-Wen
With the growing significance of public services in developed countries, there is an increased interest in the role of service innovation in governments. While most studies provide empirical analysis on how innovation serves as a promising means of improving public services, little attention has been paid to recognizing which assets and dynamic capabilities are at the heart of service innovation and how successful examples can be identified or classified. The view on this subject remains fragmented, reflecting the need to explore how institutional incentives affect public service innovation. Therefore, the focus of this study is to theorize the concept of service innovation in the public sector to achieve a consensus regarding what types of competitive strategy are the main components of innovation-based public services and to what extent their emergence can be set in motion by institutional design or policy interventions. Based on applications of the public service innovation awards launched by the central government in Taiwan, this paper illustrates the trajectory of innovation through the different approaches of public management. The methods of data collection and analyses of the award-winning agencies are outlined, followed by cluster analysis. The results of the analyses and findings are discussed, and finally, implications for theory and practice are provided.